Penyuluhan Kesehatan: Pengaruh Konsumsi Kopi Terhadap Penurunan Kadar Glukosa Darah Pada Penderita Dm Di Desa Purbawinangun Cirebon - Misika Alam; Solikhah Solikhah; Supriyatin Supriyatin; Hery Prambudi; Rizal Ibrahim Aji; Usdiyanto Usdiyanto; Renita Renita (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Cases of Diabetes Mellitus disease are increasing every year, the most vulnerable age who experience Diabetes is in the age group of 55-64 years because at this age the body's immunity begins to decline gradually, diabetics always experience an increase in blood glucose levels that exceed normal limits, one way to lower blood glucose levels in addition to taking antidiabetic drugs is to consume coffee without added sugar because it can lower blood glucose levels by Consume coffee according to the maximum recommended limit for diabetics. For diabetics, it is recommended to consume coffee with a caffeine level of 200mg or the equivalent of 2 cups of coffee per day. This activity aims to provide information that coffee can lower blood glucose levels. The community service method is carried out by observation and treatment of giving coffee and conducting blood glucose checks. The results of the observation were obtained by the number of respondents in Purbawinangun Village, Cirebon as many as 10 people with an average blood glucose level of 259 mg/dL and blood glucose levels after consuming coffee with an average value of 231 mg/dL. The conclusion is that coffee can affect the decrease in glucose levels.